2018
DOI: 10.1039/c8ob01065j
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled synthesis of polyhydroxylated bicyclic azetidines as a new class of iminosugars

Abstract: We report herein the development of a stereodivergent route towards polyhydroxylated bicyclic azetidine scaffolds, namely 6-azabicyclo[3.2.0]heptane derivatives. The strategy hinges on a common bicyclic β-lactam precursor, which is forged by way of a rare example of a cationic Dieckmann-type reaction, followed by IBX-mediated desaturation. Substrate-controlled diastereoselective oxidations then allow the divergent preparation of novel iminosugar mimics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Compain et al developed a novel class of conformationally constrained iminosugars 68-70, based on four-membered ring-containing spirocycles (Scheme 9) [146,147]. In this case, the rigid bicyclic system was conceived with the idea to reproduce the structure of bioactive iminosugars (e.g., DNJ and castanospermine), while more closely resembling the conformation of the substrates of carbohydrate-processing enzymes in their transition states [148,149]. The synthesis of 68-70 relied on the Rh(II)-catalyzed C(sp 3 )-H amination of carbamate 65 (in turn obtained from vitamin C [150]) enabling a stereoselective C-N bond formation in 66 [151,152].…”
Section: Pyrrolidine Iminosugars and Pyrrolidine-containing Bicyclic mentioning
confidence: 99%
“…Compain et al developed a novel class of conformationally constrained iminosugars 68-70, based on four-membered ring-containing spirocycles (Scheme 9) [146,147]. In this case, the rigid bicyclic system was conceived with the idea to reproduce the structure of bioactive iminosugars (e.g., DNJ and castanospermine), while more closely resembling the conformation of the substrates of carbohydrate-processing enzymes in their transition states [148,149]. The synthesis of 68-70 relied on the Rh(II)-catalyzed C(sp 3 )-H amination of carbamate 65 (in turn obtained from vitamin C [150]) enabling a stereoselective C-N bond formation in 66 [151,152].…”
Section: Pyrrolidine Iminosugars and Pyrrolidine-containing Bicyclic mentioning
confidence: 99%
“…The same authors reported the synthesis of diastereoisomers of 199 and 200 via the m-CPBA oxidation of alkene 197 which provided epoxide 201 as a single diastereoisomer in 88% yield (Scheme 32). 100 After benzylation of the hydroxymethyl group, epoxide-ring opening could be efficiently achieved, with complete regioselectivity, using catalytic sulfuric acid in acetic acid. Applying the same end game sequence used for the preparation of compounds 199-200 yielded 1-deoxygulonojirimycin bicyclic analogue 203 as well as its N-butyl derivative 204 (racemic form).…”
Section: Obnmentioning
confidence: 99%
“…Unfortunately, none of the four amino-tetrols 199, 200, 203 and 204 were potent inhibitors of any glycosidase among the test panel (Saccharomyces cerevisiae α-glucosidase, almond βglucosidase, green coffee beans α-galactosidase, E. coli β-galactosidase and Jack bean α-mannosidase). 100 In the course of their work towards the 6-azabicyclo[3.2.1]octane ring system, Grainger et al synthesized the bicyclic β-lactam diols 210 and 211 as well as triol 212 (Scheme 33). 103 Starting from compound 205, carbamoyl diethyldithiocarbamate 206 was readily prepared in two steps.…”
Section: Obnmentioning
confidence: 99%
“…9 Therefore, numerous syntheses of iminosugars have been developed to improve the potency and selectivity of these inhibitors but also to better understand the structure-activity relationships. 1c, 10 The influence of ring size and rigidity have been studied through the synthesis of 4-membered, 11 5-membered 12 and 7-membered rings, 13 through bicyclic locked deoxy-iminosugars, 14 hydrazine type bicyclic iminosugars 15 , constrained fused bicyclic iminosugars 16 or sp 2 -iminosugars. 17 Many of the reported syntheses use carbohydrates as starting materials 18 including stannylated ones 19 but others start from simple organic molecules.…”
Section: Introductionmentioning
confidence: 99%